PERAN PENGAWASAN TERHADAP PEMBAGUNAN JALAN PROVINSI DI DINAS BINA MARGA DAN BINA KONSTRUKSI UPT WILAYAH III PAREPARE KABUPATEN SIDENRENG RAPPANG - Risnataliya Risnataliya; Andi Uceng; Rahman Yaqub (PRAJA: Jurnal Ilmiah Pemerintahan, 2021)
This study aims to determine the role of supervision on the construction of provincial roads in the Department of Highways and Construction of UPT Region III Pare-Pare, Sidenreng Rappang Regency. The population and sample in this study were 32 staff of the Anabanna village office and the Anabanna village community. This study uses a quantitative approach. Data collection techniques by observation, interviews, questionnaires and documentation. The collected data were then analyzed using frequency and percentage tables. The results showed that the role of supervision of the construction of provincial roads in the Department of Bina Marga and Construction of UPT Region III Parepare, Sidenreng Rappang Regency at the Anabanna village location was good with an average percentage of 69%. Meanwhile, the factors affecting the role of supervision of provincial road construction in the Department of Highways and Construction of UPT Region III Pare-pare, Sidenreng Rappang Regency are good with an average percentage of 65% seen from Human Resources (HR), Budget / costs and Facilities. Facilities and infrastructure